Volatility Dynamics of Islamic and Conventional Equity Portfolios During COVID-19: Evidence from Fama-French and GARCH Models - Haikal, Muhammad Barry; Triandhari, Risna; Parianom, Raden (Department of Islamic Economics, IPB University, 2025)
This paper examines the performance and volatility of Islamic equity portfolios in contrast to their conventional counterparts during the pre-pandemic, COVID-19 pandemic, and post-pandemic periods. Using daily data gathered from February 2019 to December 2023, this study employs the Fama-French factor models alongside GARCH-type models to evaluate risk-adjusted returns and volatility of portfolios. Furthermore, shariah screening rules, particularly those related to debt ratios, are integrated into the portfolio construction process to assess their influence on performance. The results show that while Islamic equity portfolios generally deliver lower returns, they demonstrate significantly lower volatility. This relation implicitly suggests a trade-off between risk and return, which are amplified further during periods of market stress. These findings contribute to the growing literature on Islamic finance by demonstrating the stability provided by shariah-compliant equity portfolios. Future research may explore sector-specific performance or extend the framework to other economies.